Moderated Mediation of Ethical Considerations between Individual Values and Values in the Actual Practice of the CPA Profession - Arnold V. Salcedo (Center for Risk Management & Sustainability and RSF Press, 2021)
CPA Baby Boomers, Generation X, Generation Y or Millennials and the latest addition, Generation Z, possess unique characteristics, workplace values and ethics. This study focused on how workplace values and ethical considerations directly and indirectly affect the values of CPAs. The participants are five hundred forty-one (n=541) Baby Boomers, Generation X, Generation Y and Generation Z Filipino professional accountants among four different sectors namely the academe or education, commerce & industry, government and public practice. A partial least square-structural equation modeling (PLS-SEM) including mediation and moderation analysis were used to determine the direct and indirect effects. Using Schwartz motivational values, the study revealed that there is a positive and significant relationship between self-transcendence (benevolence and universalism) and openness to change (self-direction and stimulation) as workplace values to the values of practicing CPAs. There is a negative but significant relationship between workplace values of conservation (tradition and security) and self-enhancement values (power and achievement) with the CPA values. Also, workplace values significantly affect ethical considerations, while ethical considerations (or strict adherence to CPA’s code of ethics) significantly influence the CPA values while in practice. Lastly, the moderation analysis further revealed that workforce generation has moderating effect on the relationship between conservation values and the actual practice values. Ethical considerations have no mediating effect on the significant positive relationship between individual values and values in practice (benevolence and universalism), while workforce generations have moderating effect in the conservation values of CPAs